Three men and two women in costumes - Unknown:::Creator::::::::::::
Photograph shows three men and two women in costumes possibly for a skit or play. James Bertina and Mrs. John Goldsborough are seated at the table. Frank Bunch(?), Dr. John Goldsborough, and Moreen Futter(?) are standing around the table.